Integrating Business Principles in STEM Education: Fostering Entrepreneurship in Students and Educators in the US and Nigeria - Daniel Raphael Ejike Ewim (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Integrating business principles into STEM education is crucial for preparing students to navigate the rapidly evolving global economy driven by technological advancements and innovation. This paper explores the significance of integrating business principles in STEM education and the potential benefits for students, educators, and the economy in both the United States and Nigeria. We examine successful initiatives and programs that foster entrepreneurship among STEM students and identify best practices for effectively teaching business concepts in STEM contexts. Challenges and barriers hindering the successful integration of business principles into STEM education are also discussed, including resistance to interdisciplinary education, limited resources and support for entrepreneurship, and balancing technical and business skill development. In order to address these challenges, we propose recommendations and best practices such as adopting effective pedagogical approaches, engaging industry and community partners, and creating a supportive culture for entrepreneurship within STEM institutions. In addition, this article identifies several potential research areas for the future. These include longitudinal studies on the effects of business-integrated STEM education on entrepreneurial outcomes, comparative analyses of different approaches, and assessments of the scalability and adaptability of successful initiatives across different countries. The promotion of entrepreneurship and business skills among STEM students can enhance their employability, career prospects and contribute to economic growth. This paper urges further research and action to support the development of the next generation of STEM-educated entrepreneurs who can drive innovation and economic growth globally, both in the United States and Nigeria.